Adoptive Transfer of JC Virus‐Specific T Lymphocytes for the Treatment of Progressive Multifocal Leukoencephalopathy. Issue 4 (10th February 2021) - Berzero, Giulia; Basso, Sabrina; Stoppini, Luca; Palermo, Andrea; Pichiecchio, Anna; Paoletti, Matteo; Lucev, Federica; Gerevini, Simonetta; Rossi, Andrea; Vegezzi, Elisa; Diamanti, Luca; Bini, Paola; et al.
Abstract : Objective: Progressive multifocal leukoencephalopathy (PML) is still burdened by high mortality in a subset of patients, such as those affected by hematological malignancies. The aim of this study was to analyze the safety and carry out preliminary evaluation of the efficacy of polyomavirus JC (JCPyV)‐specific T cell therapy in a cohort of hematological patients with PML. Methods: Between 2014 and 2019, 9 patients with a diagnosis of "definite PML" according to the 2013 consensus who were showing progressive clinical deterioration received JCPyV‐specific T cells. Cell lines were expanded from autologous or allogenic peripheral blood mononuclear cells by stimulation with JCPyV antigen‐derived peptides. Results: None of the patients experienced treatment‐related adverse events. In the evaluable patients, an increase in the frequency of circulating JCPyV‐specific lymphocytes was observed, with a decrease or clearance of JCPyV viral load in cerebrospinal fluid. In responsive patients, transient appearance of punctate areas of contrast enhancement within, or close to, PML lesions was observed, which was interpreted as a sign of immune control and which regressed spontaneously without the need for steroid treatment. Six of 9 patients achieved PML control, with 5 alive and in good clinical condition at their last follow‐up. Interpretation: Among other novel treatments, T cell therapy is emerging as a viable treatment option in patients with PML, particularly for those not amenable to restoration of specific immunity. Neurologists should be encouraged to refer PML patients to specialized centers to allow access to this treatment strategy. ANN NEUROL 2021;89:769–779